miR-452 Reverses Abnormal Glycosylation Modification of ERα and Estrogen Resistance in TNBC (Triple-Negative Breast Cancer) Through Targeting UGT1A1 - Li, Yan; Zhou, Yidong; Mao, Feng; Shen, Songjie; Zhao, Bin; Xu, Yali; Lin, Yan; Zhang, Xiaohui; Cao, Xi; Xu, Ying; Chen, Chang; Zhang, Jinqian; et al. (Frontiers in Oncology, 2020)
Background: The breast epithelial cells in patients with TNBC actually have specific ER expression, the abnormal glycosylation of UGT1A1 in TNBC cells resulted in abnormal expression and function of ERα through regulating the modification of ERα. Therefore, our study target the role of UGT1A1 expression, then glycosylation modification of ERα (Estrogen receptor α) and estrogen resistance in development of TNBC. Methods: The differential expression of mRNA and miRNA in TNBC tissues was tested. Luciferase activity was analyzed in TNBC cells treated with miR-452. Moreover, the human mammary gland and TNBC cell lines were dealt with estrogen and miR-452 or its inhibitors, then proliferation ability was further determined. Moreover, the role of interaction between UGT1A1 and ERα in the glycosylation modification of ERα and UGT activity, metabolism of estrogen were assessed. The effects of miR-452 on TNBC by improving abnormal glycosylation modification of ERα by targeting UGT1A1 and estrogen resistance were studied in vitro and in vivo. Results: The expression level of UGT1A1 in TNBC tumor tissues was higher than its matched para-tumorous tissues, but the miR-452 expression was opposite. The glycosylation modification site of ERα expressed in TNBC cells was different from that of normal mammary epithelial cells. The estrogen 17β-Estradiol (E2) significantly promoted mitotic entry of TNBC cells. The interaction between UGT1A1 and ERα, which affected the expression level each other, then the UGT enzyme activity and proliferation of TNBC cells. UGT1A1 induced production of intracellular estrogens and TNBC proliferation, but it could be reverse by over-expression of ERα. Up-regulation ERα caused down-regulation of UGT1A1 and marked decrease of intracellular estrogen products, and then suppressed TNBC proliferation. Moreover, UGT1A1 was the target gene of miR-452, miR-452 antagomir restrained TNBC xenogarft. Conclusions: Our results demonstrated estrogen was the positive factor in proliferation of TNBC cells at onset of mitosis through accentuating the expression and enzyme activity of UGT1A1. But, miR-452 targeted to UGT1A1, then regulated glycosylation modification of ERα, estrogen metabolism, and TNBC development associated with estrogen resistance.